Sex Differences on Clinical Characteristics, Severity, and Mortality in Adult Patients With COVID-19: A Multicentre Retrospective Study - Sha, Jing; Qie, Guoqiang; Yao, Qingchun; Sun, Wenqing; Wang, Cuiyan; Zhang, Zhongfa; Wang, Xingguang; Wang, Peng; Jiang, Jinjiao; Bai, Xue; Chu, Yufeng; Meng, Mei (Frontiers in Medicine, 2021)
Background: Coronavirus disease-2019 (COVID-19) epidemic is spreading globally. Sex differences in the severity and mortality of COVID-19 emerged. This study aims to describe the impact of sex on outcomes in COVOD-19 with a special focus on the effect of estrogen. Methods: We performed a retrospective cohort study which included 413patients (230 males and 183 females) with COVID-19 from three designated hospitals in China with a follow up time from January 31, 2020, to April 17, 2020. Women over 55 were considered as postmenopausal patients according to the previous epidemiological data from China. The interaction between age and sex on in-hospital mortality was determined through Cox regression analysis. In addition, multivariate Cox regression models were performed to explore risk factors associated with in-hospital mortality of COVID-19. Results:Age and sex had significant interaction for the in-hospital mortality (P<0.001). Multivariate Cox regression showed that age (HR 1.041, 95% CI 1.009-1.073, P=0.012), male sex (HR 2.033, 95% CI 1.007-2.098, P=0.010), the interaction between age and sex (HR 1.118, 95% CI 1.003-1.232, P=0.018), and comorbidities (HR 9.845, 95% CI 2.280-42.520, P=0.002) were independently associated with in-hospital mortality of COVID-19 patients. In this multicentre study, female experienced a lower fatality for COVID-19 than male (4.4% vs 10.0%, P=0.031). Interestingly, stratification by age group revealed no difference in-hospital mortality was noted in women under 55 compared with women over 55 (3.8% vs 5.2%, P=0.144), as well as in women under 55 compared with the same age men (3.8% vs 4.0%, P=0.918). However, there was significantly difference in women over 55 with men of the same age group (5.2% vs 21.0%, P=0.007). Compared with male patients, female patients had higher lymphocyte (P<0.001) and high-density lipoprotein (P<0.001), lower high sensitive c reaction protein level (P<0.001), and lower incidence rate of acute cardiac injury (6.6% vs 13.5%, P=0.022). Conclusion: Male sex is an independent risk factor for COVID-19 in-hospital mortality. Although female mortality in COVID-19 is lower than male, it might not be directly related to the effect of estrogen. Further study is warranted to identify the sex difference in COVID-19 and mechanisms involved.